Wearable Real-time Mental Stress Detector - Abdul Kader, Lamis (2022)
A Master of Science thesis in Biomedical Engineering by Lamis Abdul Kader entitled, “Wearable Real-time Mental Stress Detector”, submitted in November 2022. Thesis advisor is Dr. Hasan Al-Nashash and thesis co-advisors are Dr. Usman Tariq and Dr. Fares Al-Shargie. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).